2020
DOI: 10.1111/jep.13379
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interprofessional education on healthcare providers' intentions to engage in interprofessional shared decision‐making: Perspectives from the theory of planned behaviour

Abstract: Aims and objectivesThe present study aimed to investigate the effects of interprofessional education on healthcare providers' intentions to engage in an interprofessional shared decision‐making (IP‐SDM) process at emergency department and exploring the affecting factors on their intentions.MethodsWe conducted the study through a sequential explanatory mixed method (quantitative‐qualitative) design. All ED residents and nurses from two university hospitals were invited and assigned to the intervention and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…These results are aligned with those of a recent systematic review on patient's involvement in decision-making in non-western countries that highlighted the need for healthcare professional and patient training in SDM [7]. Patients lack of familiarity with their rights and their low health literacy were acknowledged as barriers in other Iranian studies, as well [23,26]. However, further studies are required regarding which training format could work best for healthcare professionals and patients in non-western countries such as Iran, and what are the impact of these trainings on SDM implementation in long term.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are aligned with those of a recent systematic review on patient's involvement in decision-making in non-western countries that highlighted the need for healthcare professional and patient training in SDM [7]. Patients lack of familiarity with their rights and their low health literacy were acknowledged as barriers in other Iranian studies, as well [23,26]. However, further studies are required regarding which training format could work best for healthcare professionals and patients in non-western countries such as Iran, and what are the impact of these trainings on SDM implementation in long term.…”
Section: Discussionsupporting
confidence: 82%
“…The second video showed two simulated consecutive prenatal follow-up consultations during which a pregnant woman, her partner, and a healthcare professional used a PtDA about Down Syndrome prenatal screening [21,22]. Other studies which, similarly, applied vignettes for explaining SDM, showed that healthcare professionals' knowledge and intention to engage in SDM has increased [23]. Fourth, participants completed a questionnaire evaluating the 12 domains of TDF.…”
Section: Workhop Implementationmentioning
confidence: 99%
“…With the help of the theory of planned behaviour (TPB), researchers have conducted multiple studies in identifying why and how a consumer can behave sustainably (Johnstone and Lindh, 2018; Giampietri et al , 2018; Judge et al , 2019). They have provided empirical evidence for the relationship between attitude, subjective norms and perceived controlled behaviour of consumers (Keshmiri et al , 2020). So, the two approaches that deal with the understanding of consumer behaviour i.e.…”
mentioning
confidence: 99%
“…Of all the studies, 69% (36/52) were published between 2019 and 2021 [ 9 , 32 - 68 ]. Furthermore, 58% (30/52) were located in Canada [ 7 , 8 , 10 - 12 , 23 - 25 , 28 , 31 , 35 , 38 - 41 , 44 - 51 , 53 , 54 , 56 , 60 , 63 , 65 , 67 ] and the rest in the United States (n=6), the United Kingdom (n=4), Australia (n=2) [ 30 , 34 ], Iran (n=2) [ 55 , 64 ], Argentina (n=1) [ 52 ], Indonesia (n=1) [ 32 ], Germany (n=1) [ 58 ], Sweden (n=1) [ 21 ], the Netherlands (n=1) [ 59 ], and Burkina Faso (n=1) [ 37 ]. In addition, two multicountry studies were reported: 1 from Brazil-China-France-Japan-Mali [ 68 ] and 1 from Canada-Vietnam [ 19 ] ( Table 1 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%